80.6k views
0 votes
Solve the equation 3(x-6)+8=5x-6

User Notbad
by
4.8k points

2 Answers

5 votes

Answer:

x = -2

Explanation:

3(x - 6) + 8 = 5x - 6

Distribute;

3x - 18 + 8 = 5x - 6

Collect like terms;

3x - 10 = 5x - 6

Subtract 5x from both sides;

-2x - 10 = -6

Add 10 to both sides;

-2x = 4

Divide both sides by -2

x = -2

User Leftclickben
by
6.2k points
5 votes

Answer:

x=-10

Explanation:

3(x-6) +8=5x-6=

3x-18+8=5x-6=

3x-10=5x-6=

3x-5x=10-6=

-2x=4

x=-2

User Samssonart
by
6.1k points